Outage probability of multiuser cognitive MIMO system - WU Ying-xiao1; ZHU Qi2 (Tongxin xuebao)
To analyze the multi-antenna gain in multiuser cognitive radio system, a multiuser cognitive MIMO framework was presented. The outage performance was considered in the multiple-antenna flat Raleigh fading broadcast downlink channel and the closed-form expression of the outage probability of primary and secondary users was derived. The number of transmitter and receiver antenna was carefully analyzed for impacts the outage performance of the primary and secondary user. Simulation verified the theory analyses and results show that the multi-antenna gain improves the system performance.